1983
DOI: 10.1002/cne.902180403
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitecture and topographic projections of the gustatory centers in a teleost, Carassius carassius

Abstract: The neuronal connections in the central gustatory system of the crucian carp were examined by means of degeneration and HRP methods. Cell morphology in the primary gustatory lobes was studied in Golgi-impregnated material. Medium-sized neurons of the facial lobe emit axons which project to the secondary gustatory nucleus. The nucleus intermedius facialis of Herrick ('05) projects bilaterally. Large neurons send axons through the spinal trigeminal tract to terminate in the spinal trigeminal nucleus and in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
132
1

Year Published

1988
1988
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 31 publications
22
132
1
Order By: Relevance
“…The efferent projections of the secondary gustatory nucleus in Lepomis show essentially the same pattern of tertiary gustatory connections in percomorphs as has been demonstrated for cyprinids [5,6] and silurids [2]. It is surprising, that while the secondary gustatory nucleus is much smaller in Lepornis than it is in cyprinids or silurids, the tertiary gustatory nucleus is of similar dimension.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…The efferent projections of the secondary gustatory nucleus in Lepomis show essentially the same pattern of tertiary gustatory connections in percomorphs as has been demonstrated for cyprinids [5,6] and silurids [2]. It is surprising, that while the secondary gustatory nucleus is much smaller in Lepornis than it is in cyprinids or silurids, the tertiary gustatory nucleus is of similar dimension.…”
supporting
confidence: 53%
“…Although a histologically comparable nucleus cannot be recognized in cypriniform teleosts, attempts have been made to identify a homologous structure within the preglomerular complex of the latter teleosts. For example, a 'nucleus glomerulosus' in the crucian carp, Carassius carassius, has been shown to receive a tertiary gustatory projection after lesioning of, or horseradish peroxidase (HRP) injections into, the secondary gustatory nucleus [5,6]. If nucleus glomerulosus of percomorphs is homologous to this tertiary gustatory center demonstrated in Carassius, then it would consequently be expected to receive a substantial projection from the secondary gustatory nucleus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of this area in the control of feeding and aggressive behavior has been suggested by electrical stimulation experiments in cichlids [Demski and Knigge, 1971;Demski, 1973]. Gustatory inputs to this structure have been reported in acanthopterygian teleosts [sunfish : Wullimann, 1988;tilapia: Yoshimoto et al, 1998] and in ostariophysan teleosts [catfish: Kanwal et al, 1988;Lamb and Caprio, 1993;Lamb and Finger, 1996; crucian carp: Morita et al, 1980Morita et al, , 1983 for review see Meek and Nieuwenhuys, 1998]. In an acanthopterygian teleost Thamnaconus, visual inputs via the corpus glomerulosum (CG) to the inferior lobe have also been reported [Sakamoto and Ito, 1982].…”
Section: Introductionmentioning
confidence: 96%
“…In teleosts the hypothalamus is the target of multisensory convergence [Finger, 1980;Morita et al, 1980Morita et al, , 1983Wulliman, 1988;Striedter, 1990]. Keller et al [1990] identified projections from nucleus electrosensorius in the inferior lobe of Eigenmania.…”
Section: Hypothalamusmentioning
confidence: 99%